The pattern of monumental architecture of the Southern Moche territory: the nuclear area and its ends - Franco Jordán, Régulo G. (2023)
In all the territory occupied by the Moche (Piura-Huarmey), two areas have been differentiated: Northern Moche and Southern Moche. This differentiation was made based on the study of ceramic styles and forms. With the analysis of the monumental architecture, the thesis of the existence of two territorial areas of the Moche phenomenon is reinforced. There are notable differences between the models of the two areas. The main buildings in the northern area such, as the pyramids of Sipan and Fortaleza in Pampa Grande, have large volumes in the form of truncated prisms with terraces and/or platforms at different levels and intercommunication ramps, without the presence of a front ceremonial plaza, quite the opposite occurs in the southern area, where the main buildings are platforms with stepped facades, with lateral access ramp to the top and a front plaza. The model of the southern area is found in El Brujo and Huaca de la Luna (Chicama and Moche valleys) that are considered within the nuclear area. The Huacas de Dos Cabezas, to the north, and Huaca San Pedro and Pañamarca, to the south, are included as models of the extremes.